An Empirical Application and Monte Carlo Analysis of Tests of Dynamic Specification - Mizon, Grayham E.; Hendry, David F. (Review of Economic Studies, 1980)
Grayham E. Mizon, David F. Hendry; An Empirical Application and Monte Carlo Analysis of Tests of Dynamic Specification, The Review of Economic Studies, Vol